Dampak Kegiatan Jumat Bersih untuk Meningkatkan Kecerdasan Interpersonal Anak Usia Dini di RA An Najwa Garung - Chuswatun Hasanah; Robingun Suyud El Syam; Bambang Sugiyanto (Jurnal Budi Pekerti Agama Islam, 2025)
This study aims to explore the impact of the Jumat Bersih (Clean Friday) activity on enhancing the interpersonal intelligence of early childhood learners, as well as the challenges encountered during its implementation. This research employed a qualitative descriptive approach, with data collected through observation, interviews, and documentation. Observations were conducted directly and recorded on observation sheets, interviews were carried out using pre-prepared question guides, and documentation was obtained directly from the school. Data analysis utilized thematic analysis with a triangulation method. The results of the study indicate that the Jumat Bersih activity plays a significant role in facilitating the social learning process among young children. The activity supports the development of cooperation, effective communication, empathy, and conflict resolution skills. The positive impacts observed during the activity were also reflected in the children’s daily behaviors, both at school and at home. Therefore, such activities can serve as an effective learning model for strengthening interpersonal intelligence. The main challenges in implementing Jumat Bersih include differences in children’s social abilities, difficulties in guiding balanced interactions, and the need for consistent strategies from schools and teachers. However, these challenges can be addressed through appropriate approaches, active guidance, and collaboration between schools and parents